On the interpretation of changes in the subtropical oxygen minimum zone volume off Chile during two La Niña events (2001 and 2007) - Pizarro-Koch, Matías; Pizarro, Oscar; Dewitte, Boris; Montes, Ivonne; Paulmier, Aurélien; Garçon, Véronique; Sepulveda, Hector Hito; Corredor-Acosta, Andrea; Aguirre, Catalina; Ramos, Marcel (Frontiers in Marine Science, 2023)
Oxygen minimum zones (OMZs) are extended oceanic regions for which dissolved oxygen concentration is extremely low. They are suspected to be expanding in response to global warming. However, currently, the mechanisms by which OMZ varies in response to climate variability are still uncertain. Here, the variability of the subtropical OMZ off central Chile of a regional coupled physical–biogeochemical regional model simulation was analyzed for the period 2000–2008, noting that its fluctuations were significant despite the relatively weak amplitude of the El Niño/Southern Oscillation (ENSO). In particular, the interannual variability in the OMZ volume (OMZVOL, defined as the volume with dissolved oxygen concentration (DO) ≤ 45μM) was approximately 38% larger than that of the seasonal cycle, with maximum and minimum anomalies of OMZVOL taking place during two cold La Niña (LN) years (2001 and 2007). The model analyses further reveal that these anomalies resulted from a combined effect of changes in (1) the oxygen-poor waters poleward transport by the Peru–Chile undercurrent (PCUC), (2) the intensity of quasi-zonal jets influencing the transport of water to and from the OMZ, and (3) the zonal DO transport related to mesoscale eddy activity. Specifically, the interannual variability of the PCUC modulated primarily the DO contents of the OMZ core [(DO) ≤ 20μM] and secondarily the OMZVOL, while cross-shore DO transport by the zonal jets and the eddy fluxes played a major role in ventilating and shaping the offshore extent of the OMZ. When the OMZVOL was maximum (minimum), the PCUC transport was slightly increased (reduced), which was associated with a reduction (increase) in the ventilation of the OMZ through negative (positive) anomalies of zonal advection and DO eddy fluxes. Our results demonstrate that significant natural interannual variability in the subtropical OMZ off Chile originates from the interplay between oceanic equatorial teleconnection (PCUC transport) and local non-linear dynamics (the zonal jets and mesoscale eddies).